4-(5X+7)=6-(X-3)

Simple and best practice solution for 4-(5X+7)=6-(X-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-(5X+7)=6-(X-3) equation:


Simplifying
4 + -1(5X + 7) = 6 + -1(X + -3)

Reorder the terms:
4 + -1(7 + 5X) = 6 + -1(X + -3)
4 + (7 * -1 + 5X * -1) = 6 + -1(X + -3)
4 + (-7 + -5X) = 6 + -1(X + -3)

Combine like terms: 4 + -7 = -3
-3 + -5X = 6 + -1(X + -3)

Reorder the terms:
-3 + -5X = 6 + -1(-3 + X)
-3 + -5X = 6 + (-3 * -1 + X * -1)
-3 + -5X = 6 + (3 + -1X)

Combine like terms: 6 + 3 = 9
-3 + -5X = 9 + -1X

Solving
-3 + -5X = 9 + -1X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add 'X' to each side of the equation.
-3 + -5X + X = 9 + -1X + X

Combine like terms: -5X + X = -4X
-3 + -4X = 9 + -1X + X

Combine like terms: -1X + X = 0
-3 + -4X = 9 + 0
-3 + -4X = 9

Add '3' to each side of the equation.
-3 + 3 + -4X = 9 + 3

Combine like terms: -3 + 3 = 0
0 + -4X = 9 + 3
-4X = 9 + 3

Combine like terms: 9 + 3 = 12
-4X = 12

Divide each side by '-4'.
X = -3

Simplifying
X = -3

See similar equations:

| 4yx(5y-2)=122 | | -b^4+5b^2+36=0 | | 13*x+72=-23x | | p-24=19/6(18-5) | | 6x+5/x-3+x-6/3x-9 | | 4y=5y-2 | | -7x-5(-4x-11)=-101 | | 10+2x-2x=0 | | 4+2x=36 | | 6x+12=9x+17 | | p-24=19/6(h-5) | | -20+24x+9x^2=0 | | 4x^3-12X^2+20X=0 | | x+5-3x=2x+8-5x | | -4x-3(4x-2)=-86 | | 3(x+1)-4(2x-5)+10x= | | 5X+(X-3)=X-(2X+5) | | f(x)=x^2(6-x) | | 3/4(12x+32)=99 | | -49/7 | | 3+9x=57 | | -175-30x+x^2=0 | | -6x-2=-1x+3 | | (7+2I)-(3-4i)=0 | | 5x+6=48 | | 7n-(3n+8)= | | ((2x^6)/(x^4))((x^2+4x+4)/(4x^7)) | | 7b-(3b+8)= | | 5x+4=74 | | 9(x+2)=58 | | -8+10x+25x^2=0 | | 16-2(3x-1)=12-1(4-8x) |

Equations solver categories